2017
DOI: 10.1515/bot-2016-0091
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed reproductive biology: environmental and genetic controls

Abstract: Knowledge of life cycle progression and reproduction of seaweeds transcends pure academic interest. Successful and sustainable seaweed exploitation and domestication will indeed require excellent control of the factors controlling growth and reproduction. The relative dominance of the ploidy-phases and their respective morphologies, however, display tremendous diversity. Consequently, the ecological and endogenous factors controlling life cycles are likely to be equally varied. A vast number of research papers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 195 publications
(193 reference statements)
0
39
1
1
Order By: Relevance
“…Therefore, the most plausible suggestion involves epiphytic microorganisms that are found on the surfaces of seaweeds. Based on the most extensive studies of interactions between bacteria and marine green seaweeds to date (Joint et al 2007, Wichard 2015, the association of seaweeds with epiphytic bacteria is commonly thought to be essential for their normal growth, morphogenesis, and reproduction (Egan et al 2013, Singh and Reddy 2014, Wichard 2015, Liu et al 2017). In addition to exchanges of nutrient chemicals and morphological regulators (Egan et al 2013, Singh and Reddy 2014, Wichard 2015, bacterium-derived IAA is involved in bud formation in the Florideophyte Gracilaria dura (Singh et al 2011a).…”
Section: Are Phytohormones Synthesized By and Transferred From Symbiomentioning
confidence: 99%
“…Therefore, the most plausible suggestion involves epiphytic microorganisms that are found on the surfaces of seaweeds. Based on the most extensive studies of interactions between bacteria and marine green seaweeds to date (Joint et al 2007, Wichard 2015, the association of seaweeds with epiphytic bacteria is commonly thought to be essential for their normal growth, morphogenesis, and reproduction (Egan et al 2013, Singh and Reddy 2014, Wichard 2015, Liu et al 2017). In addition to exchanges of nutrient chemicals and morphological regulators (Egan et al 2013, Singh and Reddy 2014, Wichard 2015, bacterium-derived IAA is involved in bud formation in the Florideophyte Gracilaria dura (Singh et al 2011a).…”
Section: Are Phytohormones Synthesized By and Transferred From Symbiomentioning
confidence: 99%
“…While this line of research is picking up again (Oppliger et al, 2012;Bogaert et al, 2016;Martins et al, 2017) further effort should be made to develop more integrative approach with interaction experiments in ecophysiological research (Oppliger et al, 2012;Martins et al, 2017) in combination with modeling if possible. Such results should be put then in perspective with underlying molecular mechanisms (Liu et al, 2017). So far, phenological shifts in response to ocean warming have not been detected for seaweeds.…”
Section: Resultsmentioning
confidence: 92%
“…One adaptation of marine macrophytes to ensure survival in these highly dynamic and extreme habitats is a complex life cycle, with alterations in preferred conditions depending on the life history stage (Lubchenco and Cubit 1980;Cunningham et al 1993). Changing environmental conditions can be important triggers in life history events such as initiating reproduction (Liu et al 2017) and especially temperature and photoperiod have been found to be important factors in the life history of bladed Bangiales (Pereira et al 2004;Lindstrom et al 2008;López-Vivas et al 2015).…”
Section: Discussionmentioning
confidence: 99%